Medical terminology : the language of health care - Willis, Marjorie Canfield (Baltimore : Williams & Wilkins, 1996)
Presents terminology by body systems in modules that include screens on origin, anatomy, word building, context, procedures, technology, health care issues, and more. Integrates color, audio, video, animation, and interactive exercises to promote understanding.
Includes index.
Keywords: Medicine; Terminology as Topic; Terminology as Topic